2019
DOI: 10.1016/j.ijheh.2018.11.005
|View full text |Cite
|
Sign up to set email alerts
|

A Faecal Contamination Index for interpreting heterogeneous diarrhoea impacts of water, sanitation and hygiene interventions and overall, regional and country estimates of community sanitation coverage with a focus on low- and middle-income countries

Abstract: ObjectivesThe impact on diarrhoea of sanitation interventions has been heterogeneous. We hypothesize that this is due to the level of prevailing faecal environmental contamination and propose a Faecal Contamination Index (FAECI) of selected WASH indicators (objective 1). Additionally, we provide estimates of the proportion of the population living in communities above certain sanitation coverage levels (objective 2).MethodsObjective 1: Faecal contamination post-intervention was estimated from WASH intervention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 65 publications
1
37
0
3
Order By: Relevance
“…Low-income households are at greater risk from exposure, as they are more likely to be in areas affected by sewage and septage overflow during floods (Hawkins et al, 2013).The identification of locally important key fecal transmission pathways, and an understanding of a person's full exposure to fecal pathogens, can provide valuable information for the prioritization of interventions (Robb et al, 2017;WHO, 2018;Wang et al, 2018). Various studies have found that exposure and health risks are associated not only with an individual's sanitation but also the sanitation of their communities (Hunter and Prüss-Ustün, 2016;Wolf et al, 2019). For example, in Timor-Leste, although only 7% of the urban population uses toilets that flush to an open drain, 55% live in communities where at least one household uses a toilet that flushes to an open drain, potentially exposing many households in the neighborhood to pathogens (UNICEF and WHO, 2019).…”
Section: Contaminationmentioning
confidence: 99%
“…Low-income households are at greater risk from exposure, as they are more likely to be in areas affected by sewage and septage overflow during floods (Hawkins et al, 2013).The identification of locally important key fecal transmission pathways, and an understanding of a person's full exposure to fecal pathogens, can provide valuable information for the prioritization of interventions (Robb et al, 2017;WHO, 2018;Wang et al, 2018). Various studies have found that exposure and health risks are associated not only with an individual's sanitation but also the sanitation of their communities (Hunter and Prüss-Ustün, 2016;Wolf et al, 2019). For example, in Timor-Leste, although only 7% of the urban population uses toilets that flush to an open drain, 55% live in communities where at least one household uses a toilet that flushes to an open drain, potentially exposing many households in the neighborhood to pathogens (UNICEF and WHO, 2019).…”
Section: Contaminationmentioning
confidence: 99%
“…Values of this variable >0 were trichotomized into approximately equal groups, yielding groups with 1–3, 4–6, or 7–9 indications with compliant handwashing frequency. Following a practice by Wolf et al (2019b) , these choices were made subjectively “… as a simplified approach and in order to get a good distribution of scores” ( Wolf et al, 2019b , p. 272).…”
Section: Methodsmentioning
confidence: 99%
“…The Ebola outbreak in 2014–2016 undermined malaria control efforts and led to a massive increase in malaria-related illness and death in the three West African countries ( WHO, 2020c ). Safe drinking-water, sanitation and hygiene interventions may be helpful to reduce risk of faecal contamination of the living environment ( Wolf et al, 2019 ). Frequent hand-washing with soap should be adopted to prevent the spread of infection.…”
Section: Prevention and Mitigation: What Can Be Done?mentioning
confidence: 99%